2008
DOI: 10.1111/j.1440-1746.2007.04990.x
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic diagnosis of early squamous neoplasia of the esophagus with iodine staining: High‐grade intra‐epithelial neoplasia turns pink within a few minutes

Abstract: By using the pink-color sign for endoscopic diagnosis, accurate diagnosis without endoscopic biopsy for iodine-unstained areas was possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
82
1
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(89 citation statements)
references
References 21 publications
2
82
1
4
Order By: Relevance
“…After NBI examination, we switched back to WLI and sprayed 10 to 20 mL of 1.5% Lugol solution evenly over the mucosa from esophagogastric junction to upper esophagus. The criteria of suspected lesions were defined as a hyperemic change, uneven or nodularity of mucosa under WLI system (Figure  1A), or brownish discoloration of mucosa with abnormal epithelial capillary pattern (Inoue’s Classification type III ~ V) under NBI-ME system (Figure  1B and 1C) [9,10,16,17], or a well-demarcated Lugol-unstained area (Figure  1D) with a diameter greater than 5 mm or any Lugol-voiding lesions accompanied with pink-silver sign which is often associated with high-grade neoplasia [18]. Finally, the stomach, and the first and second portion of the duodenum, were examined under WLI using the typical panendoscopic procedure.…”
Section: Methodsmentioning
confidence: 99%
“…After NBI examination, we switched back to WLI and sprayed 10 to 20 mL of 1.5% Lugol solution evenly over the mucosa from esophagogastric junction to upper esophagus. The criteria of suspected lesions were defined as a hyperemic change, uneven or nodularity of mucosa under WLI system (Figure  1A), or brownish discoloration of mucosa with abnormal epithelial capillary pattern (Inoue’s Classification type III ~ V) under NBI-ME system (Figure  1B and 1C) [9,10,16,17], or a well-demarcated Lugol-unstained area (Figure  1D) with a diameter greater than 5 mm or any Lugol-voiding lesions accompanied with pink-silver sign which is often associated with high-grade neoplasia [18]. Finally, the stomach, and the first and second portion of the duodenum, were examined under WLI using the typical panendoscopic procedure.…”
Section: Methodsmentioning
confidence: 99%
“…Oesophageal HGD and carcinoma appear as non-stained areas with a pinkish colour with iodine-based chromoendoscopy 84. One observational study indicated that iodine chromoendoscopy improved lesion delineation in 88% of cases involving oesophageal HGD or SCC 85.…”
Section: Consensus Statementsmentioning
confidence: 99%
“…Shimizu et al [3] reported that HGIN could be identified as iodine-unstained areas that are more distinct and reddish than LGIN when the brown color of iodine solution in the normal region has faded after the staining. This is because there is almost no remaining glycogen-containing epithelium in HGIN.…”
Section: Lugol Chromoendoscopymentioning
confidence: 99%
“…Chromoendoscopy using iodine has been one of the most reliable diagnostic tools in detecting early SCC of the esophagus [3,4]. It has been effectively utilized not only in detecting, but also determining the local extent of the tumor.…”
Section: Introductionmentioning
confidence: 99%